ANALISIS KETERAMPILAN SOSIAL DI SDN 1 SITUSARI - Deti Siti Aisyah; Muhammad Nurjamaludin; Karantiano Sadasa Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the presence of elementary school students who still exhibit low social skills, such as difficulties in interacting, lack of empathy, and inability to cooperate effectively within the school environment. The purpose of this study is to determine the level of students’ social skills at SDN 1 Situsari. This research employed a descriptive quantitative method, with data collected through a Likert-scale questionnaire developed based on social skill indicators, including empathy, communication, cooperation, responsibility, participation, and problem-solving. The sample consisted of 30 students selected randomly. Data analysis was conducted using descriptive statistics by calculating the mean and standard deviation. The results showed that students’ social skills were generally in the good category, with an average score of 71.17. A total of 33% of students were in the good category, 30% in the fairly good category, 30% in the not good category, and 3% each in the very good and very poor categories. These findings indicate that most students have relatively adequate social skills; however, there are still students with low social skills who require further attention. Therefore, efforts from teachers and schools are needed to improve students’ social skills through appropriate learning strategies.